The role of hyperlocal media in cultural preservation: an analysis of the Three Cs implementation at Galuh Prambanan TV in Klaten - Jati, Rocky Prasetyo (ASSOCIATION FOR SCIENTIFIC COMPUTING ELECTRICAL AND ENGINEERING (ASCEE), 2024)
This paper explores implementing the